15 Management and Professional Talent Enhancement Special Programme graduands receive MBA - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PAYA BESAR, 5 November 2022 - Working and pursuing master’s study simultaneously is not an obstacle for 15 Universiti Malaysia Pahang (UMP) staff to complete the Master of Business Administration (MBA) programme on a part-time basis which was first offered specially for UMP staff.